2019
DOI: 10.7554/elife.45508
|View full text |Cite
|
Sign up to set email alerts
|

DDR2 controls breast tumor stiffness and metastasis by regulating integrin mediated mechanotransduction in CAFs

Abstract: Biomechanical changes in the tumor microenvironment influence tumor progression and metastases. Collagen content and fiber organization within the tumor stroma are major contributors to biomechanical changes (e., tumor stiffness) and correlated with tumor aggressiveness and outcome. What signals and in what cells control collagen organization within the tumors, and how, is not fully understood. We show in mouse breast tumors that the action of the collagen receptor DDR2 in CAFs controls tumor stiffness by reor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 44 publications
3
74
0
Order By: Relevance
“…We observed that fibroblasts do assemble an ECM network using exogenously supplied proteins, and the matrix network properties are dependent on the source of the FN (Figures 4-6). Past work indicates that cancer-associated fibroblasts are a major effector of ECM production and remodeling in the tumor microenvironment [7]. Fibroblasts, often resident stromal fibroblasts, transition slowly into cancer associated fibroblasts via several mechanisms, including contact signals with BC cells, physiological stress, and soluble factors from the tumor [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that fibroblasts do assemble an ECM network using exogenously supplied proteins, and the matrix network properties are dependent on the source of the FN (Figures 4-6). Past work indicates that cancer-associated fibroblasts are a major effector of ECM production and remodeling in the tumor microenvironment [7]. Fibroblasts, often resident stromal fibroblasts, transition slowly into cancer associated fibroblasts via several mechanisms, including contact signals with BC cells, physiological stress, and soluble factors from the tumor [48].…”
Section: Discussionmentioning
confidence: 99%
“…In the primary tumor, FN and collagen fibrils accumulate as the tumor develops, which causes an increase in tissue stiffness. This matrix stiffness promotes proliferation, increases tumor cell aggressiveness, and is believed to bolster the number of cancer stem cells [4,7]. Recent research has indicated that FN and collagen fibrils accumulate parallel to the primary tumor border during premetastatic growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During that interplay, the amount of fibronectin and its degree of fibrillarization within the extracellular matrix are adapted to the specific stage of progress of the disease (Figure 7). In contrast, in invasive cancers, these fibrils reorient themselves vertically to the boundary of the tumor and serve as so-called tracks for the migration of cancer cells across the basement membrane (Yang et al, 2011;Clark and Vignjevic, 2015;Bayer et al, 2019).…”
Section: Fibronectinmentioning
confidence: 99%
“…Indeed, ablation of DDRs in cancerassociated fibroblasts (CAFs) in the tumour stroma does not affect tumour growth, but prevents from lung metastasis (Corsa et al, 2016). In CAFs, DDR2 controls tumour stiffness by reorganizing the collagen fibres, thereby facilitating integrin activation at the tumour-stromal boundary and favouring cell invasion (Bayer et al, 2019). Serge Roche (CRBM, Montpellier, France) provided evidence for the therapeutic benefit of targeting DDR1 in colorectal cancer (CRC) cells.…”
Section: Targeting Ddrs In Cancer and Other Diseasesmentioning
confidence: 99%